An expert guide to planning experimental tasks for evidence-accumulation modeling - Boag, Russell; Innes, Reilly J.; Stevenson, Niek; Bahg, Giwon; Busemeyer, Jerome R.; Cox, Gregory E.; Donkin, Chris; Frank, Michael J.; Hawkins, Guy E.; Heathcote, Andrew; Hedge, Craig; Lerche, Veronika; et al. (Advances in methods and practices in psychological science, 2025)
Evidence-accumulation models (EAMs) are powerful tools for making sense of human and animal decision-making behavior. EAMs have generated significant theoretical advances in psychology, behavioral economics, and cognitive neuroscience and are increasingly used as a measurement tool in clinical research and other applied settings. Obtaining valid and reliable inferences from EAMs depends on knowing how to establish a close match between model assumptions and features of the task/data to which the model is applied. However, this knowledge is rarely articulated in the EAM literature, leaving beginners to rely on the private advice of mentors and colleagues and inefficient trial-and-error learning. In this article, we provide practical guidance for designing tasks appropriate for EAMs, relating experimental manipulations to EAM parameters, planning appropriate sample sizes, and preparing data and conducting an EAM analysis. Our advice is based on prior methodological studies and the our substantial collective experience with EAMs. By encouraging good task-design practices and warning of potential pitfalls, we hope to improve the quality and trustworthiness of future EAM research and applications.
Artikel zuerst online veröffentlicht: 27. Mai 2025
Gesehen am 25.09.2025